Strategi Guru dalam Menumbuhkan Literasi Budaya Siswa melalui Pembelajaran Budaya Banyumasan SD N 1 Karanganyar - Ratnasari, Dwi; Mareza, Lia (Universitas Sebelas Maret, 2025)
Culture in Indonesia, including traditional games, needs to be preserved through cultural literacy, as it is increasingly threatened by extinction due to technological advancement and global change. This study aims to describe the strategies employed by teachers to foster cultural literacy among students at SD N 1 Karanganyar. This research adopts a qualitative approach with a case study design. Data collection techniques include observation, interviews, and documentation. The informants in this study were the sixth-grade teacher and four sixth-grade students. The findings reveal several teacher strategies in fostering students cultural literacy through Banyumasan cultural learning, namely:a) Implementation of hands-on learning methods,b) Utilization of traditional games as learning tools, andc) Morning literacy programs. Supporting factors include the availability of reading materials in the school library and the active role of parents. The implication of this study lies in its relevance to educational policy, serving as a consideration for policymakers at both the regional and national levels to design educational policies that encourage schools to develop learning programs based on the preservation of local cultural heritage, such as Banyumasan cultural education..Budaya yang ada di Indonesia salah satunya permainan tradisional perlu dilestarikan melalui literasi budaya karena mulai punah tergerus oleh teknologi yang disebabkan oleh perubahan global. Penelitian ini bertujuan untuk mendeskripsikan strategi guru dalam menumbuhkan literasi budaya siswa SD N 1 Karanganyar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara dan dokumentasi. Informan pada penelitian ini adalah guru kelas VI dan empat siswa kelas VI. Jadi, kesimpulannya berdasarkan penelitian yang telah saya lakukan menunjukkan terdapat beberapa strategi guru dalam menumbuhkan literasi budaya siswa melalui pembelajaran Budaya Banyumasan yaitu: a. Penerapan metode praktik langsung, b. Pemanfaatan permainan sebagai alat belajar, c. Program literasi pagi. Adapun faktor pendorong yaitu tersedianya bahan bacaan di perpustakaan dan peran orang tua. Implikasi dari penelitian saya terletak pada kebijakan pendidikan sebagai bahan pertimbangan bagi pembuat kebijakan seperti pemerintah daerah dan pusat untuk merancang kebijakan pendidikan yang mendorong sekolah untuk mengembangkan program pembelajaran berbasis pelestarian warisan budaya lokal seperti pembelajaran Budaya Banyumasan.